2009
DOI: 10.1371/journal.pone.0005841
|View full text |Cite
|
Sign up to set email alerts
|

Complex Population Structure of Lyme Borreliosis Group Spirochete Borrelia garinii in Subarctic Eurasia

Abstract: Borrelia garinii, a causative agent of Lyme borreliosis in Europe and Asia, is naturally maintained in marine and terrestrial enzootic cycles, which primarily involve birds, including seabirds and migratory passerines. These bird groups associate with, correspondingly, Ixodes uriae and Ixodes ricinus ticks, of which the latter species may bite and transmit the infection to humans. Studies of the overlap between these two natural cycles of B. garinii have been limited, in part due to the absence of representati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
38
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(45 citation statements)
references
References 36 publications
(46 reference statements)
6
38
0
1
Order By: Relevance
“…Anti-Borrelia Ab prevalence in birds was highest in the Commander Islands; this is consistent with a high spirochete prevalence reported in I. uriae ticks collected from the vegetation on these islands (Comstedt et al 2009). The global and local prevalence of anti-Borrelia antibodies we observed in the North Pacific is, nevertheless, much lower than that observed in the North Atlantic for black-legged kittiwakes (global prevalence of 18.6%) and common murres (global prevalence of 77.1%) (Staszewski et al 2008).…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Anti-Borrelia Ab prevalence in birds was highest in the Commander Islands; this is consistent with a high spirochete prevalence reported in I. uriae ticks collected from the vegetation on these islands (Comstedt et al 2009). The global and local prevalence of anti-Borrelia antibodies we observed in the North Pacific is, nevertheless, much lower than that observed in the North Atlantic for black-legged kittiwakes (global prevalence of 18.6%) and common murres (global prevalence of 77.1%) (Staszewski et al 2008).…”
Section: Discussionsupporting
confidence: 89%
“…Seabirds may be particularly important in the global circulation of LB spirochetes (Olsen et al 1995); these birds are widely distributed and breed in large groups that often include a diverse range of interacting species (Schreiber and Burger 2001). The tick Ixodes uriae parasitises several of these seabird species in polar areas (Choe andKim 1987, Dietrich et al 2011) and has been shown to be infected with Bbsl in colonies of both Hemispheres (Olsen et al 1993, 1995, Gylfe et al 1999, Smith et al 2006, Duneau et al 2008, Comstedt et al 2009). However, host-dependent population structure has been found for I. uriae ticks (McCoy et al , 2005a and different local tick-seabird species combinations show variation in Bbsl infection prevalence and intensity (Gó mezDíaz et al 2010), which may influence the circulation of the pathogens within the marine system (Duneau et al 2008, McCoy 2008.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The involvement of seabirds and I. uriae (in the marine environment) in the transport of infected Borrelia garinii between the northern and the southern hemispheres was described. (Comstedt et al, 2009;Gern et al, 1998;Kurtenbach et al, 2006). In this context, it is interesting to mention that in a laboratory study, reactivation of latent Borrelia-infection could be induced in passerines experimentally submitted to stressful conditions simulating migration.…”
Section: Birds As Reservoirs For Borrelia Sppmentioning
confidence: 99%
“…The species was eventually identified as B. garinii, which has subsequently been found in seabird colonies throughout Europe and Antarctica, as well as in two colonies in North America (16)(17)(18)(19)(20). Since this discovery, B. burgdorferi sensu stricto and B. lusitaniae have also been reported in a few seabird colonies in the eastern North Atlantic (17).…”
mentioning
confidence: 96%